Experience and networked learning - Jones, Chris (Proceedings of the International Conference on Networked Learning, 2016)
This paper reviews the way experience has been understood and the research agendas associated with that understanding in networked learning. In the contemporary context the student 'experience' is part of common discourse and often associated with a consumerist discourse, especially in the UK and US. The widespread use of digital and networked technologies in education has also given rise to a de-centring of the subject and an identification of actors in network settings as hybrids of humans and machines (including software and code in this category) or including machines and objects as actors within a network. With a decentred subject does it still make sense to understand learning in terms of the subject's experience anymore? This paper explores these debates in the context of current educational discourse and in relation to prior research and theory in networked learning. Experience has a long history associated with phenomenological research and the related but distinct approach of phenomenography. It is related to central issues for education and learning, in particular the place of the individual cognising subject. Experience can be thought of as either the essential distinguishing component of the individual human subject, or experience can be understood as the subjective component of one kind of element in a wider assemblage of humans and machines. In the later understanding of experience in assemblages human experience does not separate the human actor from other actors in a network and they are understood symmetrically. It is a long standing position that the human sciences have a different relationship to their objects of study than natural sciences because the human sciences can have access to interior accounts from the objects they observe and because human subjects can behave in ways that are not predicable, replicable and which depend on an active construction of experience in the world. For networked learning the position and role of the human subject is a central concern and human-human interaction has always been considered essential. This paper reasserts the need for a proper understanding of experience and explores the place of the human subject in the developing research agendas found in networked learning.